Industrial Heritage as a Tourism Possibility - Corá, Jacqueline Maria; Bittencourt César, Pedro Alcântara; Merlotti Herédia, Vania Beatriz (Journal of Tourism, Sustainability and Well-being, 2019)
This study aims to analyze the uses of industrial heritage as a possibility for tourism. The theme is new and offers a range of alternatives for tourism as it includes, in this field, demonstrations of industry histories and their relationship between the city's past and future. The tourist possibility focused on industrial heritage shows the construction of historical heritage, its memory and identity. The object of study chosen is a former metallurgist founded one of the main industries in Brazil, located in the northeast of the state of Rio Grande do Sul and that had a strong influence on the economic development of this region. The methodological approach is descriptive and used to support the theoretical studies about heritage, memory and identity, as well as cultural tourism. The discussion about industrial heritage opens the possibility of knowing and understanding how the productive processes that collaborated for the industrial development of regions that had technologies and workforce needed to make the transformation that has occurred. Thus, it is verified that the governmental recognition of heritage can be an instrument for stimulating cultural tourism, through new uses to the industrial heritage collections.